Nitrogen management in Precision Farming by Soil Plant Analyses Development Meter - Dass, Anchal; Vyas, A. K.; Kaur, Ramanjit (Indian Farming, 2015)
For crop management by precision farming, a detailed, sitespecific information about production inputs and outputs is required. Primary nutrients in high amounts are needed by plants and a deficiency of anyone of them, restricts the plants growth. Nitrogen fertilizer is recognized as the source of nitrate contamination in ground water. Effective nitrogen management is a must for crop producers. For increasing the N use efficiency during growing season, an instrument called SPAD meter or chlorophyll meter works to be helpful in this direction.